PENGEMBANGAN ANTARMUKA WEBSITE LAYANAN DATA KESEHATAN MENGGUNAKAN METODE RAD DAN EVALUASI USABILITY SUS - Samudera Sakti, Gema; Abdam Muwakhid, Indra; Indriana Raniasmi, Prahita; Sholikun; Pandu Suhito, Hanif; Purnama Putra, Brian (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
Digital transformation encourages government institutions to provide public services through websites, including in the health sector. A health data service website should not only provide information but also be easy to use. The VERRARI website managed by the Semarang City Health Office still has limitations in navigation, responsiveness, and usability. This study aims to develop and evaluate the VERRARI user interface to improve usability. The website was developed using the Rapid Application Development (RAD) method, allowing rapid iterations and involving users from the early phase. Usability was evaluated using the System Usability Scale (SUS) on 46 active users selected through purposive sampling. The results show that the VERRARI website achieved a SUS score of 75,97 (good), indicating that interface improvements enhanced usability and user experience. This study can serve as a reference for government institutions in developing more responsive and user-friendly public service websites.   Keywords: Interface; Website; Healthcare; Rapid Application Development; Evaluation; Usability; User Experience.